The Relationship between Fiscal Decentralization and Economic Growth: A Systematic Review - Neupane, Deepak (Journal of Business and Management, 2024)
Background: Fiscal decentralization is practiced to improve the governance quality, service efficiency and promote economic growth. The process is concerned with the decentralization of both the revenue generation and expenditure responsibilities. Some regions though experience the benefits of economic growth, other face the challenges hindering its effectiveness. Objectives: The main objective of this study is to make a systematic review of the journal articles examining the relationship between fiscal decentralization and economic growth. Methods: The analysis was conducted considering the journal articles based on the quantitative analysis, published in the Google scholar database from 2000 to 2023. Preferred reporting items for systematic reviews and meta-analysis (PRISMA) was adopted as the standard in order to classify the literature into a specific database. The findings were tabulated into themes under the same regions and compared and contrasted under four sub-themes. Moreover, 35 articles focusing their study on various nations and regions were selected from 374 articles identified for the study. Results: No mutual consensus was found on the relationship between fiscal decentralization and economic growth. The findings reveal that fiscal decentralization can have mixed, linear positive, linear negative, and even non-linear relationships with economic growth. Conclusion: The effect of fiscal decentralization on economic growth differs across the regions and is shaped by governance as well as institutional quality. In Central and Eastern Europe, the outcomes are mixed. African and OECD nations generally have realized the positive benefits, especially from expenditure decentralization. South Asia and East Asia have mixed effects influenced by governance and institutional factors. In Southeast Asia and Latin America, decentralization though boosts economic growth, faces the challenges of resource inequality. JEL Classification: H77, O40, H11, C83, C18